Effect of ultrasonic modification on the protective activity of Flammulina velutipes polysaccharide to prevent ethanol-induced injury on GES-1 cells - Jinrong Xiao; Xin Chen; Jingsi Zhang; Yifan Wang; Lei Zhong; Qiping Zhan; Qiuhui Hu; Liyan Zhao (Food Science and Human Wellness)
Flammulina velutipes (F. velutipes) polysaccharides were modified by ultrasound at the rated power of 150 W and 900 W. The monosaccharide composition, ultraviolet-visible, and Fourier transform infrared spectral characteristics of F. velutipes polysaccharides (FVP) and their ultrasonic modification products (U-FVPs) were determined. The protective effects of FVP and U-FVPs on human gastric mucosal cells GES-1 were confirmed for the first time. The mole ratios of glucose and galactose were decreased and the mole ratio of mannose was increased after ultrasonic modification. Compared with the original FVP and the FVP modified by ultrasound of 150 W (U-FVP1), the FVP modified by ultrasound of 900 W (U-FVP2) could better prevent ethanol-induced damage to GES-1 cells. With increasing ultrasound intensity, the protective effect of FVPs on GES-1 cells was significantly enhanced by more effective prevention of intracellular reactive oxygen species (ROS) production and more promotion of expression of triglyceride factor 2 (TFF2), prostaglandin E2 (PGE2), epidermal growth factor (EGF), and transforming growth factor β1 (TGF-β1) mRNA. The ultrasonic modification might be an effective way to develop novel F. velutipes polysaccharides that could effectively resist the gastric injury caused by excessive alcohol consumption.